"A THOUSAND AND ONE NIGHTS" - A WONDERFUL MAST ERPIECE OF CREATION OF EASTERN PEOPLE (Scientific journal of the Fergana State University, 2023)
This article discusses the fact that the work "One Thousand and One Nights", which is a wonderful masterpiece of the creativity of the peoples of the East, is one of the rare literary monuments, and has brought a deep place in the hearts of readers for centuries. It is noted that many tales and stories of the work are very popular not only among Westerners or Easterners, but also among the Uzbek people. His wonderful and strange stories and narratives have been winning the hearts of readers for many centuries with their grace and simple language. It is explained that poetic passages were also given for the purpose. The article relies on the research and scientific views of G.A.Astanova.